Gold Catalysis: Catalyst Oxidation State Dependent Dichotomy in the Cyclization of Furan–Yne Systems with Aromatic Tethers. Issue 1 (13th November 2012) - Hashmi, A. Stephen K.; Hofmann, Julia; Shi, Shuai; Schütz, Alexander; Rudolph, Matthias; Lothschütz, Christian; Wieteck, Marcel; Bührle, Miriam; Wölfle, Michael; Rominger, Frank
Abstract Four different synthetic strategies led to a variety of furan–yne systems that contained an aryl system in the tether. Due to the short routes to these systems (four steps or less), a small library of substrates could easily be prepared. These were treated with AuCl3 or with the Gagosz's catalyst Ph3PAuNTf2 complex. The AuCl3‐catalyzed reactions delivered highly substituted fluorene derivatives, a class of compounds of great importance as precursors for luminophores with extraordinary abilities. Conversely, a different mechanistic pathway was observed with the cationic gold(I) catalyst. In the latter case, a mechanistically interesting reaction cascade initiated a formal alkyne insertion into the furyl‐sp3‐C bond, which gave indene derivatives as the final products. This new reaction pathway depends on the aromatic moiety in the tether, which stabilizes a crucial cationic intermediate as a benzylic cation.